2021
DOI: 10.1155/2021/8089293
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Higher-Risk Sexual Behavior in Some Selected African Countries

Abstract: Background. Although higher-risk sexual behavior (H-RSB) is a major contributor to the rapid rising rate of new HIV infections, there exists paucity of comprehensive evidence across the sub-Saharan African region. The purpose of this study was to determine the prevalence of H-RSB and its determinants across sub-Saharan Africa to inform policy. Method. Data were obtained from the Demographic and Health Survey (DHS) of ten sub-Saharan African (SSA) countries with their three most current DHS surveys from 2000 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…Past studies reported mixed results on the association between marital status and levels of risky sexual behavior. Different studies conducted in different parts of the globe reported that being married increased the likelihood of risky sexual behavior [ 7 – 10 ]. In Ethiopia, similarly, the 2016 EDHS reported that men who are married are more likely to have more than one partner in the past 12 months than those who were never married (4% compared to 2%) [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Past studies reported mixed results on the association between marital status and levels of risky sexual behavior. Different studies conducted in different parts of the globe reported that being married increased the likelihood of risky sexual behavior [ 7 – 10 ]. In Ethiopia, similarly, the 2016 EDHS reported that men who are married are more likely to have more than one partner in the past 12 months than those who were never married (4% compared to 2%) [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Globally (2019), female sex workers have been identified among the population at the highest risk of contracting and spreading the HIV virus [5][6][7]. Additionally, studies conducted by Shava and others on HIV, confirmed the high incidence and prevalence of the disease among FSW [7][8][9][10][11][12][13][14][15][16][17]. In 2020, key populations (sex workers, gay men, men who have sex with men, transgender people, people who inject drugs, and people in prisons and others) and their sexual partners accounted for 65% of global new HIV infections, of which 8% were sex workers [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…There are different predictors of HIV prevalence which depend on country and context. Some of these predictors include inconsistent condom use (people who do not use condoms always) and having multiple sexual partners [12][13][14]. According to Fauk et al, personal (lack of knowledge of HIV testing and HIV and AIDS service and lack of knowledge of the existence of HIV infection), social (fear of stigma and discrimination), and healthcare provision (lack of trust, fear of disclosure of their HIV status by health professionals and limited availability of medications) barriers associated with HIV testing among male clients contribute to the high prevalence of HIV among FSW [17].…”
Section: Introductionmentioning
confidence: 99%